(untitled) (Research, Society and Development, 2020)
Objective: To report a clinical case of the use of fiberglass pin and composite resins for oral rehabilitation of tooth 14 (upper right premolar). Case Report: A patient sought care at a private dental office complaining about a tooth with aesthetic impairment. Exposing the forms of treatment, the patient agreed to rehabilitate tooth 14 with a fiberglass pin and composite resin. It started by dismantling 2/3 of the vestibular canal to install the pin, then after its preparation, it was cemented with dual resin cement in A3 color and adapted to the root canal. Thereafter, a 37% phosphoric acid for 40 seconds was used, then the adhesive and light cured for 40 seconds. Then the crown was reconstructed with small increments photoactivated with composite resins for dentin in color A3 and enamel in color A3. A pre-finishing was done with a diamond tip and the final polishing was done after 48 hours. Conclusion: Composite resins associated with prefabricated fiberglass pins are a satisfactory alternative for the rehabilitation of endodontically treated teeth that have little remaining dental structure.